THE LEARNING MODEL OF MADHHAB TYPOLOGY NU-MUHAMMADIYAH IN ISLAMIC RELIGIOUS EDUCATION - Rahmat, Munawar; Fahrudin, Fahrudin (Universitas Pendidikan Indonesia, 2018)
Abstract. Khilafiah (the difference's of teachings) NU-Muhammadiyah has been known by the Muslim community of Indonesia. However, some students still question these differences. They question why in Islam many madhhabs, why Muslims do not agree in a single madhhab. The study aims to produce a learning model of madhhab typology NU-Muhammadiyah to improve students' understanding and acceptance of the variety of madhhabs of Islam. The research method used quasi experiment with one-sample t-test. The study found, the learning model of madhhab typology NU-Muhammadiyah proved to improve students' understanding and acceptance of different madhhabs. By exploring the different religious views between these two madhhabs the students are shown to have sufficient understanding of some of the religious issues of the two madhhabs' perspectives. They can also accept the teachings and the presence of NU and Muhammadiyah. However, the acceptance of these two jam`iyah did not indicate that the students had an inclusive and tolerant attitude to the variety of madhhabs of Islam.